2020
DOI: 10.1002/jcp.29486
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell‐conditioned media: A novel alternative of stem cell therapy for quality wound healing

Abstract: Mesenchymal stem cells‐conditioned media (MSCs‐CM) contains several growth factors and cytokines, thus may be used as a better alternative to stem cell therapy, which needs to be elucidated. The present study was conducted to evaluate the therapeutic potential of caprine, canine, and guinea pig bone marrow‐derived MSCs‐CM in excision wound healing in a guinea pig model. MSCs were obtained from bone marrow, expanded ex vivo and characterized as per ISCT criteria. CM was collected assayed by western blot to asce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 42 publications
2
60
0
1
Order By: Relevance
“…This feature has been indicated in the previous research that found that CM obtained from BM-MSC significantly accelerated scratch wound closure in L929 fibroblasts and HaCaT keratinocytes, supporting the application of MSC-CM as a therapeutic agent in cutaneous wound healing [26]. Accordingly, the latest study by Joseph et al also found that MSC-CM can be used to improve the quality of wound healing with minimal scar formation [2]. Using CM from MSC culture increases fibroblast and basal cell proliferation, collagen synthesis, and improve vascularization in the process of skin wound healing [9,11].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…This feature has been indicated in the previous research that found that CM obtained from BM-MSC significantly accelerated scratch wound closure in L929 fibroblasts and HaCaT keratinocytes, supporting the application of MSC-CM as a therapeutic agent in cutaneous wound healing [26]. Accordingly, the latest study by Joseph et al also found that MSC-CM can be used to improve the quality of wound healing with minimal scar formation [2]. Using CM from MSC culture increases fibroblast and basal cell proliferation, collagen synthesis, and improve vascularization in the process of skin wound healing [9,11].…”
Section: Discussionsupporting
confidence: 57%
“…Skin injuries are the most commonly found injury caused by blisters, burns, cuts, and ulcers of various severities [1]. If left untreated, any skin injury can interfere with its protective function and cause body tissues to be easily exposed to mechanical damages and microbial infections [2]. Other problems that may accompany wound healing are excessive healing, delayed wound healing, or lack of skin appendages [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…research study performed by Joseph et al reported that even allogenic and xenogenic use of MSC-derived conditioned media from caprine, canine, and guinea pig bone marrow could be a suitable option for healing wound defects with decreased scar production(1). The study by Joseph demonstrated that MSC-derived conditioned media may be considered an alternative for stem cell-based therapy to facilitate quality wound healing(1).…”
mentioning
confidence: 99%